Attitude and perceptions of Malay Muslim students towards educational loan repayment: a qualitative approach / Shafinar Ismail, Maheran Katan and Roaimah Omar - Ismail, Shafinar; Katan, Maheran; Omar, Roaimah (Division of Research and Industry Linkages , UiTM Melaka, 2014)
This study investigates the attitude and perceptions on educational loan repayment among Malay Muslims in Malaysia. Researches in the realm of educational loans have identified several factors contributing to defaults and repayments. These include the characteristics of students as they begin college, such as family income, race/ethnicity and students college experiences-in-terms-of-the type of institution, field of study and educational outcomes. However, no studies have so far explored the attitude and perceptions on educational loan repayment among Malay Muslims. The study adopts a qualitative methodology that involves focus groups and semi structured interviews. The respondents are the final year degree students in one public university in Malaysia. The results show that attitude and perceptions have influence educational loan repayment among Malay Muslims.